Regulation and the Sociopathic Firm - Daneke, Gregory A. (Academy of Management Review, 1985)
This paper draws on observations in abnormal psychology and evolutionary economics to develop a conceptual framework of the sociopathic organization. This framework explains certain failures in the socialization of modem firms. It is suggested that the framework be applied in exploring whether such failures are related to government regulation. Preliminary observations indicate that rather than providing for social learning, government intervention may in fact exacerbate sociopathic behavior by organizations.